TAX PLANNING AND FIRMS’ LIQUIDITY - .N1NWAOBIA Appolos; O, JAYEOBA, Olajumoke. (IJRDO - Journal of Business Management, 2016)
Tax expense is a significant cost to organizations as it affects their cash flow and working capital. As a result of this, organizations all over the world adopt tax planning strategies targeted at minimizing their tax liability without adversely affecting the overall financial liquidity of the firm. Thus, this study empirically examined the effect of tax planning strategies on firms’ liquidity. Various tax planning strategies were discussed but the strategies of Capital Intensity (CAPINT), Thin Capitalization (TINCAP), Lease Option (LOPT) and Industry sector incentives (IND) were selected as the independent variable. The Criterion variable used was firms’ liquidity measured in this study by the Current Ratio (CR) while firm size (SIZE) was adopted as the control variable. Data obtained from 154 firm- year observations were described and regression analysis was used to test the hypothesis developed. The results reveal that tax planning strategies of Capital Intensity (CAPINT), Thin Capitalization (TINCAP), and Lease Option (LOPT) exert negative effects on firms’ liquidity while tax planning strategies of Industry (IND) and firm size (SIZE) have positive effects on firms’ liquidity. This implies that tax planning as a balancing act requires possession of specialist knowledge and skills to effectively craft in order for it to positively impact firms’ liquidity as well as enhance firm value. Thus, it was recommended that appropriate measures and skill should be applied in determining appropriate mix of strategies to adopt for tax planning purpose as some strategies if not properly designed and applied may reduce tax liability at the expense of firm’s liquidity.